1983
DOI: 10.1002/tea.3660200907
|View full text |Cite
|
Sign up to set email alerts
|

Student control ideology and the science classroom environment in urban secondary schools of sudan

Abstract: An examination was made concerning the relationships between Sudanese secondary science teachers' pupil control ideology and their students' perceptions/observations of the psychosocial environment of their science classrooms. One hundred secondary science teachers were classified as possessing humanistic (N = 20) or custodial (N = 20) control ideologies. A class (N = 40) of students was randomly selected for every teacher in both groups. The findings revealed that no significant relationships existed between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Numerous studies have investigated the interactive relationships among teaching styles, aggregate characteristics of students, perceived class climate, and students' achievement and affective outcomes. Directive teachers have been found to foster classroom environments high on control, competition, and task orientation (Shultz, 1982) whereas less directive and more humanistic teachers tend to develop classes high in affiliation, involvement, teacher support, clarity, and innovation (Harty & Hassan, 1983;Moos & Trickett, 1987). While teachers bring their own styles to classroom interactions, aggregate characteristics of students "pull" for teacher behavior and class climates (Moos, 1979); for example, teacher control tends to be higher in classes with more male students (Moos & Trickett, 1987).…”
Section: Importance Of Classroom Intervention Environment For School-mentioning
confidence: 99%
“…Numerous studies have investigated the interactive relationships among teaching styles, aggregate characteristics of students, perceived class climate, and students' achievement and affective outcomes. Directive teachers have been found to foster classroom environments high on control, competition, and task orientation (Shultz, 1982) whereas less directive and more humanistic teachers tend to develop classes high in affiliation, involvement, teacher support, clarity, and innovation (Harty & Hassan, 1983;Moos & Trickett, 1987). While teachers bring their own styles to classroom interactions, aggregate characteristics of students "pull" for teacher behavior and class climates (Moos, 1979); for example, teacher control tends to be higher in classes with more male students (Moos & Trickett, 1987).…”
Section: Importance Of Classroom Intervention Environment For School-mentioning
confidence: 99%
“…Use of CES dimensions as predictor variables has established relationships between the nature of the classroom environment and science students' achievement of several inquiry skills and science-related attitudes (Fraser & Fisher, 1982). In studies that have used the actual version of the CES as a source of criterion variables, Trickett (1978) reported differences between five types of public schools (urban, rural, suburban, vocational, and alternative); Evans and Love11 (1979) reported differences among classes following alternative educational programs or innovations; Trickett, Trickett, Castro, and SchaBner (1982) found differences between single-sex and coeducational schools; and Harty and Hassan (1983) reported differences between the classes of Sudanese teachers with different student control ideologies. In studies that made use of both the actual and preferred versions of the CES in the same investigation, systematic differences were reported between students' and teachers' perceptions of actual and preferred classroom environment Fraser, 1982); Fraser and Fisher (1983b) found that students achieved better when there was a higher similarity between the actual classroom environment and that preferred by students; and Fraser and Fisher (1986) made use of learning-environment assessments in practical attempts to improve science classrooms.…”
Section: Classroom Environment Assessmentsmentioning
confidence: 99%
“…This comprehensive set of studies has investigated whether classroom environment is influenced by important factors such as class size (Walberg, 1969), gender of the teacher (Lawrenz & Welch, 1983), the subject being studied (Kuert, 1979), and teacher control ideology (Harty & Hassan, 1983).…”
Section: Desirable Future Research Directionsmentioning
confidence: 99%